Buddhism after Mao negotiations, continuities, and reinventions - Ji, Zhe; Fisher, Gareth; Laliberté, André 1959- (University of Hawai'i Press, 2019)
Buddhism under Jiang, Hu, and Xi: the politics of incorporation -- Administering bodhisattva Guanyin's island: the monasteries, political entities, and power holders of Putuoshan -- Spiritual technologies and the politics of Buddhist charity -- Tourist temples and places of practice: charting multiple paths in the revival of monasteries -- Bridging the gap: Chan and Tiantai Dharma lineages from Republican to post-Mao China -- "Transmitting the precepts in conformity with the Dharma": restoration, adaptation, and standardization of ordination procedures -- Schooling Dharma teachers: the Buddhist academy system and Sangha education -- A study of Laynuns in Minnan, 1920s-2010s: Buddhism, state institutions, and popular culture -- Urban restructuring and temple agency: a case study of the Jing'an temple -- Places of their own: exploring the dynamics of religious diversity in public Buddhist temple space -- Cyberactivities and "civilized" worship: assessing contexts and modalities of online ritual practices
Includes bibliographical references and index
Keywords: Geschichte 1970-2019; Buddhismus; China; Buddhism / China / History / 1949-; Aufsatzsammlung